The Effects of Increased Intensity and Number of Repetitions of Training on SJFT in Juniors and Cadets - Amel Mekić; Elvira Nikšić; Edin Beganović; Merima Merdan; Hadis Ramić (JUMORA: Jurnal Moderasi Olahraga, 2022)
This study aims to determine the effects of a program based on a progressive increase in the number of nage-komi repetitions (throws) on a specific judo fitness test (SJFT). The research was conducted on a total of 20 respondents. In SJFT for research purposes, 12 variables. Descriptive statistics and paired t-tests for dependent samples of initial and final testing were used for data processing. The results of the study showed significant statistical deviations in the number of throws in the first 15 seconds, with the pulse measured immediately after testing and the SJFT index (p <005). There is a noticeable need for a table to classify SJFT results for young judoists. Based on the obtained results, we can conclude that the programmed activity had positive effects on the results of the SJFT, ie that the index was statistically significantly lower in the final than in the initial testing. Taking into account the results obtained, calculated by the SPSS 22 t-test for dependent variables, the values ??of the young judoist index and the values ??of the senior index show noticeable differences. While their results can be classified into appropriate categories, the results of young judoists can be classifieclassifiedrity, under, ad and the rest as very bad. Some results could not even be ranked, so we conclude that it is necessary to make tables for classifying the results of young judoists. The obtained results can be used as guidelines for more efficient programming of the training process. Keywords: cadets, judo, juniors, SJFT test, training.